(untitled) (Journal of actual problems of jurisprudence, 2019)
It is provided measures for consideration of the main problems arising in connection with validity period of the employment contract, creation of the individual employment contract, possibility of establishment of a probation period in case of acceptance for work, contents of the individual employment contract according to the service record.